State Capitalism In The Tourism Sector: Mandalika Special Economic Zone Study - Dwi Setiawan Chaniago; Heru Nugroho; M.Falikul Isbah (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
This research observes the transformation process of tourism development governance that leads to strengthening the role of state capitalism. This research describes the regulatory trajectory of state capitalism in the tourism sector in three eras of government and identifies the style of state capitalism and its implications for the development of the Mandalika Special Economic Zone. This research uses a qualitative method with data collection techniques in the form of in-depth interviews and secondary data review. This research is analyzed from the perspective of technocratic state capitalism. The results of this study show that the regulatory trajectory in the three eras of government contributed to regulatory instrumentation in supporting state capitalism in the Mandalika tourism sector. The active role of the state in building the power of state capitalism in the development of the mandalika area is seen from several aspects including the creation of a policy framework, the provision of regulatory instruments, the provision of infrastructure as well as the main driver of economic activity in the region. The practice of state capitalism in the operationalization of the Mandalika SEZ is characterized by developmental state capitalism. This practice has succeeded in encouraging regional infrastructure development by absorbing investment while mobilizing State-Owned Enterprises in various strategic sectors such as construction, financing and financing guarantees, and Tourism SOEs. In conclusion, the development of state capitalism in the tourism sector goes hand in hand with the development of the tourism economy as one of the sectors that support Indonesia's economic growth.